Quality evaluation of salak peel tea under various drying temperatures and durations - Anggela, Anggela; Parameswari, Gusti Revalina (Department of Agricultural Products Technology, Mulawarman University, 2026)
Salak peel, commonly discarded as agricultural waste, contains bioactive compounds that can be developed into functional food products, such as herbal tea. The quality of this tea is significantly influenced by the drying process, particularly in terms of temperature and drying duration. This study investigated the effects of different drying temperatures and durations on the sensory and nutritional characteristics of salak peel tea. Drying was carried out at three temperature levels (60, 70, and 80°C) combined with six drying durations (2, 4, 6, 8, 10, and 12 h). Sensory attributes, including color, aroma, and taste, were evaluated, and the data were analyzed using factorial ANOVA, followed by Duncan’s multiple range test at a 5% significance level. The findings revealed that temperature and drying time significantly affected the sensory quality of the salak peel tea. The optimum conditions were observed at 70°C for 4 h, producing scores of 3.8, 3.76, and 3.5 for color, aroma, and taste, respectively. Proximate analysis of the best treatment indicated a moisture content of 3.85%, ash of 5.77%, protein of 0.55%, fat of 0.06%, and carbohydrate of 89.77%. These results suggest that drying at 70°C for 4 h is the most suitable treatment for producing salak peel tea with desirable sensory characteristics and proximate composition.